1991
DOI: 10.1063/1.348140
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structures of actinide materials by pulsed neutron diffraction (invited)

Abstract: We describe some attempts to observe magnetic structure in various actinide (5f-electron) materials. Our experimental technique is neutron powder diffraction as practiced at a spallation (pulsed) neutron source. We will discuss our investigations of α-Pu, δ-Pu, α-UD3, and β-UD3. β-UD3 is a simple ferromagnet: Surprisingly, the moments on the two nonequivalent uranium atoms are the same within experimental error. α-UD3, α-Pu, and δ-Pu are nonmagnetic, within the limits of our observations. Our work with pulsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…While earlier works, cited in ref. [1], assume ferromagnetic ground state and Curie temperature coinciding with that of β-UH 3 , a later neutron diffraction work concluded that it is non-magnetic [2]. That would seriously contradict to the concept of U magnetism depending mainly on the 5f-5f overlap.…”
Section: Introductionmentioning
confidence: 87%
“…While earlier works, cited in ref. [1], assume ferromagnetic ground state and Curie temperature coinciding with that of β-UH 3 , a later neutron diffraction work concluded that it is non-magnetic [2]. That would seriously contradict to the concept of U magnetism depending mainly on the 5f-5f overlap.…”
Section: Introductionmentioning
confidence: 87%
“…While earlier works, reviewed in Ref. 2, deduced magnetic ordering with T C coinciding with that of β-UH 3 , in a later neutron diffraction work it was identified as non-magnetic 15. That would seriously contradict to the concept of the U magnetism depending on the 5 f -5 f overlap.…”
Section: Introductionmentioning
confidence: 92%
“…The originally proposed ferromagnetism 12 was later taken as due to the impurity of β-UH 3 . 14 This would require that both αand β-UH 3 should have the same T C value (Curie temperature), which looked unlikely from the point of view of structure differences. Only recently the stabilization of α-UH 3 by Zr alloying confirmed that both phases are very similar, with almost identical magnetic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Even more problematic was synthesis of α-UH 3 , existing as a transient species, converting fast into β-UH 3 . The originally proposed ferromagnetism was later taken as due to the impurity of β-UH 3 . This would require that both α- and β-UH 3 should have the same T C value (Curie temperature), which looked unlikely from the point of view of structure differences.…”
Section: Introductionmentioning
confidence: 99%